ChemInform Abstract: Stereodynamic Properties of Medium‐Ring Benzo‐Fused Nitrogenous Heterocycles: Benzodiazepines, Benzazepines, Benzazocines, and Benzazonines. Issue 9 (4th March 2014) - Ramig, Keith
Abstract Review: 55 refs.